INNOVATION IN CLUSTERING TO ACHIEVE PRODUCTIVE AND AUTONOMOUS RESOURCE MOBILIZATION AT THE VILLAGE LEVEL: A CASE STUDY IN REJOWINANGUN VILLAGE - Ameylia Puspita Rosa Dyah Ayu Arintyas; Raihan Chaerani Putri Budiman (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Villages are continuously encouraged to innovate as a manifestation of good governance and excellent public service. One such innovation that has successfully emerged is clustering. In this research, we focus on the clustering innovation implemented in Rejowinangun Village, Yogyakarta. Clustering is applied to group five areas based on their leading potentials: Cultural Village, Craft Village, Herbal Village, Culinary Village, and Agro Village. The goal is to centralize development and inventory the existing potentials. Therefore, this study aims to analyze and evaluate the implementation of clustering innovation in Rejowinangun Village to achieve the mobilization of productive and autonomous resources. The research method used is a qualitative approach. Data were obtained through site observation, in-depth interviews with the Head of Rejowinangun Village, and literature documentation. The results of the study show that clustering in Rejowinangun facilitates targeted program planning and development, accelerates the development of local potentials, and improves community welfare through more effective collaboration and product marketing. Clustering also enhances resource allocation efficiency and the productivity of leading sectors. Moreover, clustering encourages collaboration among residents and strengthens local economic networks, ultimately increasing the economic independence of Rejowinangun and making it an autonomous region.